Variabilidade espacial dos atributos físicos em um Argissolo Vermelho sob floresta - Campos, Milton César Costa; Soares, Marcelo Dayron Rodrigues; Santos, Luis Antonio Coutrim; Oliveira, Ivanildo Amorim [UNESP]; De Aquino, Renato Eleoterio [UNESP]; Bergamin, Anderson Cristian (My University, 2013)
This study aim to evaluate the spatial variability of soil physical attributes in of Alfissol forest in Manicoré region, AM. The mapping of an agroforestry growing area of 70×70m was made using a regular grid sampling of 10 × 10m. In each grid, soil samples were collected at 0.0-0.2 and 0,40-0,60 m depth, with a total of 128 sample points. Physical analyses were made (texture, soil bulk and particles density, macro and microporosity, total porosity and aggregates stability in water). With the exception of DMG, DMP and class aggregates <1.00 mm had all the physical attributes spatial dependence structure ranging from moderate to weak. Values were above the range established in the mesh (12.00 to 45.56 m), enabling to make a basis for future studies in forest area. The physical attributes presented in kriging maps different spatial behavior, however there are relationships between these attributes shown by geostatistics proving that this is effective tool for studies in forest area.
Spatial dependence of soil physical attributes in of Alfissol forest
Keywords: Geostatistics; Native forest; Spatial dependence